Hydrolysis of Sago Starch by Aspergillus Awamori for the Production of a Generic Fermentation Medium - Mohd Akhir, Sobri (2004)
The efficiency of several amylolytic-enzyme-producing fungi such as Aspergillus niger, Aspergillus awamori and Aspergillus flavus to hydrolyse cooked sago starch has been carried out in shake flask cultures. Subsequently, the performance of microbial hydrolysis of sago starch by A. awamori, which was an industrial strain used for glucoamylase production, into fermentable sugar was studied in shake flask culture and 2 L stirred tank fermenter. The influence of medium composition (different types and concentrations of starch and nitrogen sources) on the rate of hydrolysis and fermentable sugar production was first carried out using shake flask cultures. The performance of microbial hydrolysis was also carried out in different modes of bioreactor operation (batch, repeated batch and continuous operation) using freely suspended cell system. Beside rate and degree of starch conversion, the enzymes produced during growth were also determined. For comparison, two-steps enzymatic hydrolysis which involve liquefaction and saccharification steps, was also carried out in batch and continuous processes. The microbial hydrolysis of gelatinised sago starch to fermentable sugar by three strains of amylolytic-enzyme-producing fungus (A. awamori, A. flavus and A. niger) was successfully carried out at low temperature (30oC) in a single step process. However, the performance of the hydrolysis by A. awamori, in term of yield (0.59 g glucose/g starch) and overall productivity (0.42 g glucose/L.h), was higher than other strain. In addition, the yield of microbial hydrolysis of the different starches (sago, potato, corn and tapioca starch) by A. awamori was more or less the same, ranged from 0.56 to 0.59 g glucose/g starch. From this study it was also found that the individual concentration of nitrogen and starch influenced glucoamylase production, and thus the efficiency of starch hydrolysis to fermentable sugar, to a greater extent than the carbon to nitrogen (C/N) ratio. The optimized medium formulation for high performance of starch hydrolysis was by using sago starch ranged from 50 to 100 g/L, yeast extract as the sole nitrogen source and C/N ratio of 17.13. The yield of glucose produced based on starch used in continuous microbial hydrolysis using 2 L stirred tank fermenter was lower than that obtained in batch hydrolysis (0.58 and 0.92 g/g, respectively) but the overall productivity was higher than that obtained in batch hydrolysis (1.44 and 0.58 g/L.h, respectively). The yield and overall productivity for microbial hydrolysis were lower than for enzymatic hydrolysis (0.75 g/g and 4.4 g/L.h, respectively). However, substantially high amount of biomass was also produced during microbial hydrolysis which can be used as nitrogen sources for media formulation. The optimum dilution rate and starch concentration for enzymatic hydrolysis using stirred tank was obtained at 0.125 h-1 and 300 g/L, respectively. On the other hand, the optimum dilution rate and starch concentration for microbial hydrolysis was obtained at 0.022 h-1 and 30 g/L, respectively. In addition, microbial hydrolysis was carried out at lower temperature (30oC) than that required in enzymatic hydrolysis (60-95oC). Thus, large reduction of operating cost is possible. Once, sterilised the glucose produced in outflow of the continuous microbial hydrolysis can be used as a generic medium for various fermentation processes.